Evaluation of emergency general surgery operations in COVID-19 patients in a pandemic hospital: a single center experience - Hasirci, İsmail and Ulutas, Mehmet E. and Simsek, Gurcan and Sahin, Alpaslan and Arslan, Kemal and Eryilmaz, Mehmet A. (International Surgery Journal, 2021)
Background: During the pandemic, the decision on delaying elective surgeries was implemented country-wide, and emergency surgeries were excluded from this scope. In this study, the patients diagnosed with COVID-19 and who underwent an emergency general surgery operation were evaluated regarding indications, demographic characteristics, and preoperative and postoperative clinical features. Methods: In the study, emergency surgeries performed by the department of general surgery between 1st June and 30th September, when our center cared only patients diagnosed with COVID-19, were reviewed retrospectively. Results: A total of 13 patients, 7 women and 6 men, were included in this study. The most common surgical diagnosis was acute appendicitis (9/13). For all of the patients with appendicitis, a conventional appendectomy procedure was performed. 2 patients were diagnosed with an incarcerated femoral hernia and then operated (2/13). One patient was operated on due to a sharp object injury, and one due to an acute abdomen caused by a perforation. Only 3 of the operated patients developed postoperative wound site complications (23%). No mortality was observed by the end of a 15-day follow-up. Conclusions: The most common cause of emergency surgeries during the pandemic, changelessly, remains to be acute appendicitis. Besides, cases of trauma, perforated peptic ulcer, and incarcerated hernia are also commonly encountered. While the pandemic continues full steam, these conditions that are associated with the pandemic but among causes of mortality and morbidity other than COVID-19 and that may require an emergency surgery should be considered. All emergency surgical procedures should continue to be performed punctually by using necessary protective types of equipment.